Trimerization of the N-terminal tail of Zika virus NS4A protein : a potential in vitro antiviral screening assay - To, Janet (2021)
The nonstructural (NS) protein NS4A in flaviviruses is a membrane protein that is critical for virulence, and, among other roles, it participates in membrane morphogenesis. In dengue virus (DENV), the NS4A hydrophilic N–terminal tail, together with the first transmembrane domain, is involved in both homo-oligomerization and hetero–oligomerization with NS4B. In both DENV and Zika virus (ZIKV), this N-terminal tail (residues 1–48) forms a random coil in solution but becomes mostly α-helical upon interaction with detergents or lipid membranes. Herein, we show that a peptide from ZIKV NS4A that spans residues 4–58, which includes most of the N–terminal tail and a third of its first transmembrane domain, forms homotrimers in the absence of detergents or liposomes. After interaction with the latter, α–helical content increases, consistent with binding. The oligomeric size of NS4A is not known, as it has only been reported in SDS gels. Therefore, we propose that full-length NS4A forms homotrimers mediated by this region, and that disruption of the oligomerization of peptide ZIKV NS4A 4–58 in solution can potentially constitute the basis for an in vitro assay to discover antivirals.